Demencia, estigma y arteterapia - Diane Waller (Arteterapia)
This paper is based on a three phase research project lasting for nine years which investigated the effectiveness of art therapy groups for older people with dementia. It consisted of a pilot lasting for one year, a two-year random control group study and a qualitative analysis of the material from the project as a whole. It proposes that the culture of exclusion which applies to older people in general is much worse for those with mental health problems, and for thosewith dementia is can be catastrophic.